English English: Pengembangan Skala Pengasuhan Berkesadaran pada Anak Prasekolah (MPP) - Afifah At Thohiroh; Mutia Aulia Dewi; Dewi Maulina; Nabilah Maghfirah Maulani; Riska Faradila; Tahlia Latifah (Faculty of Social Science and Human Ecology, IPB University, 2025)
Existing measurements of mindful parenting primarily focus on parenting in infants or older children and are designed specifically for mothers. The current study aims to develop a scale to assess mindful parenting in preschool children aged 3 to 5 (Mindful Parenting in Preschoolers/MPP) using a situational judgment test that can be completed by both parents. A total of 307 Indonesian parents aged 24–54 years old (M = 33.1, SD = 4.73) completed the 42 pooled items of the MPP. Psychometric testing was conducted to obtain the final version of the MPP with 30 items. Factor analysis revealed a three-factor structure, awareness, compassion, and non-reactivity, differing from the proposed model. Overall, the MPP demonstrates good internal consistency, and validity testing showed a significant negative correlation with parenting stress as a convergent criterion. The statistical performance of individual dimensions remains inadequate following scale reduction, necessitating further refinement and additional data collection. Despite these limitations, the MPP is a promising tool that offers a different test format compared to most currently available mindful parenting measurements.